The Meaning Of Tabarruj In The Perspective Of Indonesian Mufasirs (Schleiermacher Hermeneutics Analysis) - Riza Lailaturohmah; Eka Prasetiawati; Ikhwanuddin Ikhwanuddin (International Journal of Research, 2023)
This article discusses tabarruj from the perspective of Indonesian mufasirs. Nowadays, women are often considered tabarruj when they leave the house adorned. However, not all women understand this. As a first step in contributing to the existing problems, we try to respond to the phenomenon with theological glasses, namely contextual interpretation of tabarruj verses. However, we limit this research to QS. al Nur [24] : 31, QS. al Nur [24] : 60 and QS. al Ahzab [33] : 33 by Hamka and Bisri Mustafa. The method used is thematic method by making Schleiermacher's hermeneutics as the analysis knife. This research looks for how the Indonesian mufasir views tabarruj and what if the interpretation is read through Schleiermacher's hermeneutic criticism. The result of this study is the concept of tabarruj according to the interpretation of Hamka and Bisri Mustafa is that it does not stop at the meaning of adornment. But more than that, both of them present the context of adornment that should be done by a woman. So if you look at the current social setting in Indonesia, this interpretation is still relevant to be applied.